Student Perspective in Using Social Media As a Tool in English Language Learning - SYOFIANIS iSMAIL; Marhamah Ahmad; Muhammad Zaim; Mukhaiyar Mukhaiyar; Nurhizrah Gistituati (J-SHMIC : Journal of English for Academic, 2019)
Abstract—Learning a foreign language by using social media at the University level is very important because social media has great potential to support student-centered learning as they are flexible, interactive, and resource–rich in nature. One of its drawbacks is the quality of online instruction that lead to unfavorable perception and perspective of the students. The objectives of this research are to analyze the students’ perceptions and perspectives in using Social Media as a tool in English Language learning. Qualitative and quantitative data were collected from the students of the English Study Program, Faculty of Education, the Islamic University of Riau. Research finding revealed that social media is very practical and useful for getting general information, knowledge and to increase their language competency. Keywords — social media, perspective, language